Consumers' Knowledge, Attitudes, and Practices Toward Medicine Price Transparency at Private Healthcare Setting in Malaysia - Ahmad, Nur Sufiza; Hatah, Ernieda; Jalil, Mohamad Ridha; Makmor-Bakry, Mohd (Frontiers in Public Health, 2021)
Background: Medicine price transparency refers to the practice of making prices available to consumers for them to identify, compare, and select the medicine that provides the desired value. This study aimed to evaluate consumer knowledge, attitudes, and practices regarding Malaysia's medicine price transparency initiative, as well as factors that may influence related good consumer practices in private healthcare settings. Methods: A cross-sectional, self-administered survey was conducted between May and July 2019 among consumers attending private healthcare institutions in Malaysia. The self-developed and validated survey consisted of four sections on the following: respondents' demographics, and 28 close-ended and graded Likert scale answer options on knowledge, attitudes, and practices toward medicine price transparency. Factors influencing good consumer practices toward the transparency initiative were modeled using binary logistic regression. Results: A total of 679 respondents were part of the study. The mean age of respondents was 38 ± 13.3, with the majority (n = 420, 61.9%) being female. The respondents' mean score of knowledge and attitudes toward the price transparency initiative was 5.6 ± 1.5 of the total score of 8 and 31.9 ± 4.0 of the total score of 40, respectively. The respondents had the lowest score in the practice of price transparency, with a mean score of 31.5 ± 5.6 of the total score of 60. Male gender, Chinese ethnicity, high score on knowledge and attitudes, and high expenses on medicines influenced respondents' good practices of medicine price transparency. Conclusion: Respondents had good knowledge and attitudes, but their usage and implementation of the medicine price transparency initiative was still inadequate. A number of factors influence this inadequacy, including gender, race, consumers' out-of-pocket spending on medication, and knowledge of and attitudes toward price transparency practices. Consumer-driven market price control would be impossible to achieve without the good consumer practices of medicine price transparency.